FORMULATION AND EVALUATION OF SITAGLIPTIN PHOSPHATE GASTRO RETENTIVE TABLETS - Keerthi Brahmandam, Krishna; Kothamasu, Sasikanth; Makineni, Anitha; Nama, Sreekanth (Caribbean Journal of Sciences and Technology, 2014)
The purpose of the present investigation is to formulate a novel gastro retentive system, floating tablets of Sitagliptin Phosphate, an anti diabetic agent by direct compression technique using lactose as diluent. The drug-excipients interaction was ruled out through FTIR studies. Nine formulations of Sitagliptin Phosphate tablets were prepared using HPMC K100 and HPMC K4M as release retarding agents in different concentrations of 10, 15 and 20% w/w. The prepared batches were evaluated for organoleptic properties, hardness, friability, weight variation and in vitro drug release. All the formulations showed low weight variation with rapid dispersion time and rapid in vitro dissolution. One amongst nine promising formulations, the formulation prepared by using 15% of HPMC K100 emerged as overall the best formulation. This optimized formulation showed good release profile with complete drug release with in 24 hours. It was concluded that floating tablets of Sitagliptin Phosphate can be successfully formulated by using release retarding polymers.